Digital Signal Processing Using Matlab and Wavelets - Michael Weeks (Electrical engineering series., 2007)
Designed for upper division engineering and computer science students as well as engineers, this work emphasizes the practical applications of signal processing. Over 100 Matlab projects and wavelet techniques provide the applications of DSP, including image processing, games, filters, transforms, networking, parallel processing, and sound